A hot rolling process design optimization method for high corrosion resistance and high strength dual-phase high entropy alloy material
By optimizing the hot rolling process design of the biphasic high-entropy alloy material, including homogenizing heat treatment, hot rolling, annealing and water quenching, the problem that the hot rolling process may reduce the alloy ductility or corrosion resistance is solved, and the effect of high corrosion resistance and high strength-ductility is achieved.
Patent Information
- Application Number
- CN202411423312.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-10-12
AI Technical Summary
While increasing the hardness and strength of the alloy, the hot rolling process may reduce its ductility or corrosion resistance, and different process parameters will affect a variety of properties and require design optimization to avoid negative effects.
The hot rolling process design optimization method is adopted for a high corrosion resistance and high strength dual-phase high-entropy alloy material, including homogenizing heat treatment, 8-pass hot rolling process, annealing treatment and room temperature water quenching in an argon atmosphere to improve the mechanical properties and corrosion resistance of the alloy.
By optimizing process parameters, the mechanical properties of the alloy are significantly improved and its corrosion resistance is slightly improved, and a two-phase high-entropy alloy material with high corrosion resistance and high strength-ductility is obtained.
Smart Images

Figure CN119287286B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of alloy materials, and in particular relates to a hot rolling process design optimization method for a high-corrosion-resistant and high-strength dual-phase high-entropy alloy material. Background Art
[0002] Among the wide variety of material systems, it is important to understand the microstructural evolution of engineering materials during preparation and thermomechanical processing. In modern industry, the efficient and large-scale production characteristics of thermomechanical processing (hot rolling, forging, extrusion, etc.) play a pivotal role in the metal manufacturing industry.
[0003] Generally speaking, hot rolling increases the hardness and strength of the alloy, but may reduce its ductility or corrosion resistance. During the processing, some microscopic effects such as residual stress, microcracks, etc. are generated in the microstructure. Therefore, different hot rolling processing parameters may produce different strengthening effects. In order to obtain different properties, full attention should be paid to the evolution of microstructure, dynamic recovery and recrystallization, crystal texture, etc. The hot rolling process may also produce phase transformation and twinning induced plasticity (TRIP and TWIP) behavior. Due to this feature of TRIP and TWIP effects in coordinating the microstructure and properties of engineering materials, especially in terms of synergistic strength-plasticity, many metal materials with TRIP / TWIP effects show remarkable mechanical properties, such as TRIP / TWIP steels, nickel-based or nickel / cobalt-based superalloys, and TRIP / TWIP titanium alloys. In recent years, high entropy alloys (HEAs) have become important new materials due to their excellent high strength, wear resistance, corrosion resistance, fatigue and fracture resistance, and thermal stability. Among HEAs, Cantor (Co-Cr-Fe-Ni-Mn isoatomic alloy system) and Cantor-like alloys (Co-Cr-Fe-Ni-Mn non-isoatomic alloy system) are the most important representatives. Therefore, TRIP / TWIP HEAs become new materials with coordinated high strength-ductility, especially for fcc+hcp dual-phase Fe-based or Co-based HEAs.
[0004] Since hot rolling process parameters can affect a variety of properties, special attention should be paid to the design and optimization of the process parameters to avoid possible negative effects. Summary of the invention
[0005] In view of the above technical problems, the present invention proposes a hot rolling process design optimization method for a highly corrosion-resistant and high-strength dual-phase high-entropy alloy material. The present invention optimizes a series of processes such as hot rolling, annealing and quenching to improve its mechanical properties and corrosion resistance. The inventors optimized the process of two highly corrosion-resistant alloys designed in the previous work, characterized the microstructure and texture of the hot-rolled alloys, and tested and analyzed the corrosion and mechanical behaviors. The hot-rolled alloy under the optimized parameters has strong corrosion resistance, strength and plasticity, and is expected to become a new type of structural material.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A hot rolling process design optimization method for a high-corrosion-resistant and high-toughness dual-phase high-entropy alloy material comprises the following steps:
[0008] In an argon atmosphere, the alloy was subjected to homogenization heat treatment and quenched to room temperature;
[0009] The cooled alloy was heated to 1100°C and kept at this temperature for 30 min, and then hot rolled at 1100°C for 8 passes;
[0010] The obtained sample is annealed and then water quenched at room temperature to obtain a dual-phase high entropy alloy material;
[0011] Among them, the nominal alloy composition (atomic percentage, i.e. at%) is Co 47.5 Cr 30 Fe 7.5 Ni 7.5 Mn 7.5 or Co 46 Cr 30 Fe 7.5 Ni 7.5 Mn 7.5 Mo 1.5 .
[0012] Furthermore, the homogenization heat treatment is specifically: keeping warm at 1200° C. for 2 hours.
[0013] Furthermore, the hot rolling process is as follows: the alloy thickness before hot rolling is 10 mm, the thickness of the alloy is reduced by 0.61 mm in a single pass, the thickness of the sample is 5.1 mm after 8 passes of hot rolling, and between each pass, the alloy is heated and kept warm at 1100° C. in a furnace for 1 min.
[0014] Furthermore, the annealing treatment is specifically: annealing treatment at 900 or 1200° C. for 2 hours.
[0015] Furthermore, the alloy is formed by melting high-purity metal in a corundum crucible, and the size of the corundum crucible is: outer diameter×thickness×height=φ27mm×2.5mm×105mm.
[0016] The present invention also provides a dual-phase high-entropy alloy material prepared by the method.
[0017] Compared with the prior art, the present invention has the following advantages and technical effects:
[0018] The present invention uses Co 47.5 Cr 30 Fe 7.5 Ni 7.5 Mn 7.5 and Co 46 Cr 30 Fe 7.5 Ni 7.5 Mn 7.5 Mo 1.5 As alloy raw materials, both homogenized annealed alloys and hot rolled alloys show high corrosion resistance and high strength-ductility. Hot rolling process significantly improves mechanical properties and slightly improves corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings that constitute part of this application are used to provide a further understanding of this application. The illustrative embodiments of this application and their descriptions are used to explain this application and do not constitute an improper limitation on this application. In the drawings:
[0020] Figure 1 It is a schematic diagram of the alloy rolling process of the present invention;
[0021] Figure 2 Computational predictions for designing alloy phase diagrams; vertical cross-section of the Co-Cr-Fe-Ni-Mn-Mo system (x(Fe)=x(Ni)=x(Mn)=7.5at%x(Cr)=30at%), and phase fraction-temperature diagrams for A4 and A5 compositions;
[0022] Figure 3 is the XRD pattern of the alloy;
[0023] Figure 4 is the ECCI image of the alloy; the dark gray and light gray represent the fcc parent phase and hcp martensite phase, respectively;
[0024] Figure 5 The electrochemical test of the alloy samples was carried out in 3.5wt% NaCl solution at 1 atmosphere and room temperature; wherein, (a1) is the 2D version of the polarization curves of the 6 alloy samples after 1 hour OCP; (b1) is the 2D version of the cyclic polarization curves of the 6 alloy samples after 1 hour OCP; (c1) is the Nyquist plot of the impedance experimental data of the 6 alloy samples after 1 hour OCP; (c2) is the Bode plot of the impedance experimental data of the 6 alloy samples after 1 hour OCP;
[0025] Figure 6 Hardness and compression test data of 6 alloy samples; Vickers hardness (a), engineering stress-strain curve (b1) and true stress-strain curve (b2). DETAILED DESCRIPTION
[0026] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0027] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0028] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0029] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0030] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0031] A hot rolling process design optimization method for a high-corrosion-resistant and high-toughness dual-phase high-entropy alloy material comprises the following steps:
[0032] (1) Preparation of alloy: In a vacuum induction melting furnace, in a pure Ar atmosphere, high-purity metal (>99.9%) was used to melt the alloy in a corundum crucible to obtain Co 47.5 Cr 30 Fe 7.5 Ni 7.5 Mn7.5 and Co 46 Cr 30 Fe 7.5 Ni 7.5 Mn 7.5 Mo 1.5 Two alloys; the size of the corundum crucible is φ27mm (outer diameter) × 2.5mm (thickness) × 105mm (height); the specific melting method adopts conventional experimental operations in this field to obtain the target alloy. The preparation of the alloy is not an innovative point of the present invention and will not be described in detail.
[0033] (2) Hot rolling process:
[0034] S1. In an argon atmosphere of a vacuum furnace, the alloy is subjected to homogenization heat treatment at 1200°C for 2 h and quenched to room temperature;
[0035] S2, heating the cooled alloy to 1100°C and keeping the temperature for 30 minutes, and then performing 8 hot rolling processes at 1100°C; the thickness reduction of a single pass is 0.61mm, and between two passes, the alloy is heated and kept in a furnace at 1100°C for 1 minute;
[0036] S3. The obtained sample is annealed at 900°C or 1200°C for 2 hours, and then water quenched at room temperature to obtain a dual-phase high entropy alloy material.
[0037] The present invention also provides a dual-phase high-entropy alloy material prepared by the method.
[0038] Co used in the present invention 47.5 Cr 30 Fe 7.5 Ni 7.5 Mn 7.5 and Co 46 Cr 30 Fe 7.5 Ni 7.5 Mn 7.5 Mo 1.5 It is a fcc (face-centered cubic) + hcp (hexagonal close-packed) dual-phase cobalt-based high-entropy alloy.
[0039] Unless otherwise specified, the "room temperature" in the present invention refers to 25°C.
[0040] The raw materials used in the present invention are all purchased from the market.
[0041] The technical solution of the present invention is further illustrated by the following embodiments.
[0042] Example 1
[0043] use Figure 1The process shown prepared 6 alloys (in the figure, A4 (hs) and A5 (hs) represent the homogenization of the alloy, that is, process I; A4 (900) and A5 (900) represent the alloys after processes I, II and III'; A4 (1200) and A5 (1200) represent the alloys after processes I, II and III'). The specific operations are:
[0044] A hot rolling process design optimization method for a high-corrosion-resistant and high-toughness dual-phase high-entropy alloy material comprises the following steps:
[0045] (1) Preparation of alloy: In a vacuum induction melting furnace, in a pure Ar atmosphere, a high-purity metal (>99.9%) was melted in a corundum crucible (size: outer diameter × thickness × height = φ27 mm × 2.5 mm × 105 mm) to obtain Co 47.5 Cr 30 Fe 7.5 Ni 7.5 Mn 7.5 and Co 46 Cr 30 Fe 7.5 Ni 7.5 Mn 7.5 Mo 1.5 Two alloys;
[0046] (2) Hot rolling process:
[0047] S1. In an argon atmosphere in a vacuum furnace, the alloys were placed at 1200°C (T homo ) for 2 h and quenched to room temperature to obtain alloy A4 (Co 47.5 Cr 30 Fe 7.5 Ni 7.5 Mn 7.5 ) and A5(Co 46 Cr 30 Fe 7.5 Ni 7.5 Mn 7.5 Mo 1.5 );
[0048] S2, heating the two alloys after cooling to 1100°C and keeping the temperature for 30 minutes, and then performing 8 hot rolling processes at 1100°C; the thickness of the alloy is reduced by 0.61mm after each pass, and the alloy is heated in a furnace at 1100°C for 1 minute between two passes;
[0049] S3, the samples obtained in step S2 are placed at 900°C (T pre ) for 2 h, and then quenched in water at room temperature to obtain dual-phase high entropy alloy materials, named A4 (900) and A5 (900) respectively;
[0050] S4, the samples obtained in step S2 are placed at 1200°C (i.e., T anne ) for 2 h and then water quenched at room temperature to obtain dual-phase high-entropy alloy materials, which were named A4(1200) and A5(1200), respectively.
[0051] The material prepared in Example 1 was tested for performance, and the test method was as follows:
[0052] The composition and microstructure of the melted and hot rolled alloys were studied by electron channel contrast imaging (ECCI) and X-ray diffraction (XRD). ECCI was performed using a field emission scanning electron microscope Zeiss Sigma 300 system (Zeiss, Germany). XRD was performed using an X-ray diffractometer (RINT-TRⅢ, Rigaku SmartLab, Japan) and a 1D high-speed / resolution silicon strip detector (D / teXUltra) using Cu-Kα (wavelength λ = 1.5406).
[0053] The corrosion resistance of the alloy was studied by three electrochemical test techniques: polarization / cyclic polarization and electrochemical impedance spectroscopy (EIS). The electrochemical test was performed by an electrochemical workstation (CHI760E, China).
[0054] The compression test was performed by a laboratory equipment electromechanical material testing system (MTS C45.105, USA) with a loading speed of 0.02 mm / s and a sample size of 4.5 mm (length) × 4.5 mm (width) × 10 mm (height). The test standard is GB / T7314-2017, "Method for room temperature compression test of metallic materials". The hardness was automatically tested by a MHVS-1000 digital Vickers hardness tester under a load of 50 g. Each sample was tested 10 times in parallel to obtain the average value and standard deviation of the hardness measurement.
[0055] Test results:
[0056] 2. Calculation and characterization
[0057] In order to predict the microstructure and phase transformation and optimize the deformation heat treatment parameters in this work, CALPHAD calculations were performed in Thermo-Calc software to combine the corresponding thermodynamic and kinetic databases.
[0058] The temperatures for homogenization, preheating, and annealing are selected based on thermodynamic calculations, i.e., T homo , T pre and T anne Using the calculated vertical cross-sections and equilibrium phase fractions at different temperatures, see Figure 2. It can be seen that the homogenization heat treatment, hot rolling and annealing processes of A4 and A5 alloys are all carried out in the fcc single phase region. In order to study the influence of different alloying elements on the stability of fcc and hcp phases, the corresponding alloy system was designed. From a thermodynamic point of view, when the Cr content of the designed cobalt-based high entropy alloy is 0-40at.%, there is a possibility of phase transformation from high-temperature single-phase fcc to low-temperature hcp martensite phase, and a TRIP strengthening effect is produced, synergizing high strength-high ductility. It can also be observed from the phase diagram that within the selection range of the optimal Cr content, bcc phase and sigma brittle phase may appear. The equilibrium phase diagram of phase fraction and temperature shows that the sigma phase of A4 alloy begins to precipitate from 800℃. From the phase diagram of A5, it can be seen that the precipitation temperature of sigma phase increases after adding Mo element. In order to avoid the appearance of sigma phase, the heat treatment process is to homogenize the cast alloy at 1200℃ for 2h and then quench it in water to room temperature. The characteristic temperature and phase composition of hot rolling are also shown in the figure.
[0059] according to Figure 3 XRD, Figure 4 From the ECCI, it can be seen that the fcc+hcp dual-phase structure is the same as that of the cobalt-based high-entropy alloy designed in the inventors' previous work, and the hot rolling process produces more martensite in the deformed alloys (i.e., A4(900), A5(900), A4(1200), and A5(1200)) compared with the undeformed alloys (i.e., alloys A4(hs) and A5(hs)). In other words, a thermally induced martensitic phase transformation is formed in the homogenized samples, and a thermally induced martensitic phase transformation and a deformation-induced martensitic phase transformation are simultaneously generated in the hot-rolled samples. Figure 4 It can be clearly observed that the lath martensite after hot rolling is finer, the grains are smaller, and the dislocation slip direction is affected by the crystal texture behavior.
[0060] 3. Corrosion behavior of hot-rolled samples
[0061] Plastic deformation caused by hot rolling usually produces some defects, such as residual stress, microcracks, and micro-decohesion at the interface of inclusion / solid solution phase or passivation layer / matrix phase. These factors often lead to the deterioration of certain properties (such as poor ductility and reduced corrosion resistance). Therefore, annealing and other processes are required after the hot rolling process to eliminate its negative effects. Therefore, the present invention performs two annealing processes, III' / III" after the hot rolling process.
[0062] The corrosion behavior of the hot-rolled samples was evaluated by electrochemical tests, including polarization, cyclic polarization, and impedance tests (i.e. Figure 5 (a)-(c) in the figure. Figure 5(a1) is the potentiodynamic polarization curve of the alloy in solution. As shown in the figure, except for the A4 alloy, the other alloys do not show obvious activation-passivation zone, indicating that the alloy can spontaneously passivate in the natural state, forming a dense passivation film on the surface, and the alloy passivation zone is stable. corr ) has little change. From the local enlarged diagram of the breakdown potential, it can be seen that the pitting corrosion resistance of HEAs in the A5 system with the addition of Mo element is better than that of the A4 system as a whole. One important reason is that Mo oxide is produced in the passivation film, thereby improving the pitting corrosion resistance of the alloy.
[0063] The cyclic potentiodynamic polarization experimental data are shown in Figure 5 As shown in (b1) in the figure. The cyclic polarization curve shown in the figure shows that the passivation window of the A5 series is smaller than that of the A4 series, indicating that the repassivation ability of the alloy passivation film is stronger. This is consistent with the results obtained by the dynamic potential polarization test.
[0064] Figure 5 (c1) and Figure 5 (c2) in the figure shows the impedance spectrum of HEAs in 3.5wt.% NaCl solution after rolling and different heat treatment temperatures, (c1) is the Nyquist diagram, and (c2) shows the Bode diagram and phase angle diagram. It can be seen from the Nyquist diagram that all HEAs show a curve of a single capacitive arc. It can be clearly seen that after rolling, the radius of the capacitive arc of the alloy sample becomes larger, among which the capacitive arc of A5 (900) is the largest, indicating that the interface has a higher charge transfer resistance and stronger passivation film protection. It can also be found from the Bode diagram that the impedance modulus of the A5 series is higher than that of the A4 series as a whole, which is consistent with the distribution law of the Nyquist diagram. At the same time, the phase angle maintains a large angle (a large angle indicates that the passivation film maintains a higher stability).
[0065] These electrochemical test and analysis data show that the hot rolling + annealing process does not reduce the corrosion resistance, confirming that the hot rolling process parameter optimization method of the present invention is reliable for improving the corrosion resistance of the two alloys.
[0066] 4. Mechanical properties of hot rolled samples
[0067] The mechanical properties of the dual-phase high entropy alloy prepared in Example 1 were tested, and the experimental data of compression and hardness tests are as follows: Figure 6As shown. It can be seen that the alloy is initially in the elastic strain stage, at which time the stress and strain are in a linear relationship, which conforms to Hooke's law. The stress limit and fracture strain of sample A4 before hot rolling are 1180.2MPa and 46.46%, the stress limit and fracture strain of sample A4(900) after hot rolling are 1661.23MPa and 65.34%, and the stress limit and fracture strain of A4(1200) are 1536.46MPa and 57.38%. Compared with the corresponding experimental data of A4(hs) before hot rolling, the hardness / engineering stress limit / engineering strain of A4(900) and A4(1200) increased by about 14.9% / 40.76% / 40.95% and 12.7% / 30.17% / 228.4%, respectively. Compared with A4, the overall performance of A5 is higher than that of A4. The stress limit and fracture strain of sample A5(hs) before hot rolling are 1418.33MPa and 49.24%, the stress limit and fracture strain of A5(900) are 2142.99MPa and 78.65%, and the stress limit and fracture strain of A5(1200) are 1716.97MPa and 64.44%. Compared with the performance of A5(hs) before hot rolling, the hardness / engineering stress limit / engineering strain of A5(900) and A5(1200) increased by about 9.4% / 51.13% / 59.76% and 7.7% / 20.9% / 31.30%, respectively. In particular, A5(900) achieved the best balance between strength and toughness. That is, the compressive strength and plasticity of alloys A4 and A5 after hot rolling and annealing are greatly improved, indicating that the optimization process of these two cobalt-based high-entropy alloys with fcc+hcp structure has achieved a synergistic effect of high strength and high plasticity. The currently designed composition and processing technology confirm that the TRIP effect is an effective way to balance strength-ductility.
[0068] 5. Phase transition induced phase transition behavior
[0069] In the present invention, due to the low stacking fault energy of the fcc phase, the fcc to hcp martensitic phase transformation occurs through quenching and deformation heat treatment, that is, the dual-phase structure is the fcc parent phase (i.e., soft phase) and the hcp martensitic phase (i.e., hard phase). In the compression test, due to the different deformation behaviors of the soft phase and the hard phase, the alloy with a dual-phase structure acts as an elastic-plastic body, and the deformation behavior is divided into three stages. The first stage is the elastic stage, and the soft phase and the hard phase are both elastic relationships with linear deformation; the second stage is the elastic-plastic stage, at this time, the soft phase and the hard phase undergo plastic and elastic deformation respectively; the third stage is the two-phase plastic deformation stage. From Figure 4 and 6 It can be seen that the increase of martensite phase and the refinement of laths make the alloy show higher strength and ductility.
[0070] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A hot rolling process for a high corrosion-resistant and high-toughness dual-phase high-entropy alloy material, characterized in that: The following steps are involved: In an argon atmosphere, the alloy was subjected to homogenization heat treatment and quenched to room temperature; The cooled alloy was heated to 1100°C and kept at this temperature for 30 min, and then hot rolled at 1100°C for 8 passes; The samples obtained by the hot rolling process were subjected to two annealing processes and then water quenched at room temperature to obtain a dual-phase high-entropy alloy material; Wherein, the alloy is Co 47.5 Cr 30 Fe 7.5 Ni 7.5 Mn 7.5 and Co 46 Cr 30 Fe 7.5 Ni 7.5 Mn 7.5 Mo 1.5 ; The hot rolling process is as follows: the alloy thickness before hot rolling is 10 mm, the thickness of the alloy is reduced by 0.61 mm in a single pass, and the thickness of the sample after 8 passes of hot rolling is 5.1 mm. Between each pass, the alloy is heated and kept at 1100° C. in a furnace for 1 minute; The annealing treatment is specifically: treating at an annealing temperature of 900° C. or 1200° C. for 2 hours.
2. The hot rolling process of the high corrosion-resistant and high-toughness dual-phase high-entropy alloy material according to claim 1 is characterized in that: The homogenization heat treatment is specifically: keeping the temperature at 1200° C. for 2 hours.
3. The hot rolling process of the high corrosion-resistant and high-toughness dual-phase high-entropy alloy material according to claim 1 is characterized in that: The alloy Co 47.5 Cr 30 Fe 7.5 Ni 7.5 Mn 7.5 and Co 46 Cr 30 Fe 7.5 Ni 7.5 Mn 7.5 Mo 1.5 It is made by vacuum melting high-purity metal in a corundum crucible. The size of the corundum crucible is: outer diameter × thickness × height = φ27mm × 2.5mm × 105mm.
4. A dual-phase high entropy alloy material prepared by the method according to any one of claims 1 to 3.
Citation Information
Cited By
AI-driven anti-corrosion high-entropy alloy material process optimization method and system
CN122046748A